Relationship between exercise capacity, endothelial progenitor cells and cytochemokines in patients undergoing cardiac rehabilitation - Cesari, Francesca; Sofi, Francesco; Caporale, Roberto; Capalbo, Andrea; Marcucci, Rossella; Macchi, Claudio; Lova, Raffaele Molino; Cellai, Tommaso; Vannucci, Mauro; Gensini, Gian Franco; Abbate, Rosanna; Gori, Anna Maria (Thrombosis and Haemostasis, 2009)
No data are available about the possible role of endothelial progenitor cells (EPCs), cytochemokines and N-terminal pro-brain natriuretic peptide (NT-proBNP) in determining a different response to short period of cardiologic rehabilitation (CR), as measured by the improvement of exercise capacity. In a population of 86 cardiac surgery patients, we evaluated the numbers of EPCs, pro- and anti-inflammatory cytokines (IL-6,IL-8, IL-10, IL-1ra), hs-C-reactive protein (CRP), vascular endothelial growth factor (VEGF) and NT-proBNP before (T1), and after 15 days of CR (T2). EPCs were measured by flow cytometry, and the exercise capacity was measured at T1 and T2 by using the six-minute walk test (6MWT). At T2, a significant increase of 6MWT (p<0.0001) was detected. No significant increase of EPCs was observed, while a significant (at least p<0.05) decrease in cytochemokines, CRP and NT-ProBNP levels was evidenced. By analyzing the median improvement of 6MWT, only patients with a median improvement ≥23% showed a significant (p<0.05) increase of EPCs at T2, with significant correlations between EPCs, VEGF and IL-10. On the contrary, in patients with a median improvement <23% a negative correlation between CRP and EPCs was observed. Finally, CD34+/KDR+ EPCs showed significant correlation with IL-8 at T1. In conclusion, a short period of CR intervention determines a different pattern of modifications for EPCs in relation to the improvement of exercise capacity.
Keywords: Endothelial progenitor cells; cytochemokines; cardiac rehabilitation; exercise capacity